Endoscopic Variceal Ligation and ß-Blocker Combination Versus Ligation Monotherapy as Variceal Esophagus Bleeding Secondary Prevention - Kevin Varian Marcevianto; Marcellus Simadibrata (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2019)
Background: Variceal esophagus' risk of re-bleeding in the first year is 60-70%. Mortality rate of acute bleeding is 20-35%. Latest guidelines of esophageal rupture suggest endoscopic ligation and Non-selective b-Blocker combination for re-bleeding prevention. However, monotherapy still can be chosen, depends on the clinical judgement and patient preference. The previous meta-analysis still gave inconclusive results on therapy combination effectivity. Moreover, there is no side effect discussion between both treatment choices. Hence, this evidence-based case report analyses the effectivity of combination treatment for esophageal bleeding secondary prevention.Method: Literature searching in Scopus, ProQuest, PubMed, ScienceDirect, and EBSCOhost used keywords and their synonyms. Three articles selected included two meta-analyses and one RCT. Critical appraisal on validity, importance, and applicability based on Oxford Center of EBM 2011 was conducted.Results: Two meta-analysis prove treatment combination is significantly effective decreasing variceal re-bleeding. Ravipati et al. results in RR 0.601 (95% CI 0.44 - 0.82). However, Kumar et al. shows non-significant result. On the other hand, three articles show that therapy combination failed to significantly lower the mortality rates RR 0,786 (95% IK 0,45 - 1,39). This is due to the limitation of treatment combination to prevent cirrhotic progression and other complications. Moreover, this also is due to contraindications and non-suitability of the patients toward non-selective b-Blocker in 30-40% cases.Conclusion: Endoscopic ligation and non-selective b-Blocker combination is recommended for variceal esophagus bleeding secondary prevention, but other treatments are needed to lower the mortality rate1.